Let $$S_n=\sum_{i=1}^{n}\sin k,\quad S_0=0.$$


$$\sum_{k=1}^{n}\frac{\sin k}{k}=\sum_{k=1}^{n}\frac{S_k-S_{k-1}}{k}=\frac{S_n}{n}+\sum_{k=1}^{n-1}\frac{S_k}{k(k+1)}.$$

Could someone please explain the steps in getting this last equality. I am told it is using Abel's summation, but I have been reading up on that and I still can't see it.


Let $a(n)$ and $f(n)$ be sequences and $A(n) = \displaystyle \sum_{k=1}^{n} a(k)$.

Abel's partial summation technique: \begin{align*} \sum_{n=1}^{N} a(n) f(n) & = \sum_{n=1}^{N} f(n) (A(n)- A(n-1)) = \sum_{n=1}^{N} A(n) f(n) - \sum_{n=1}^{N} A(n-1) f(n)\\ & = \sum_{n=1}^{N} A(n)f(n) - \sum_{n=0}^{N-1} A(n) f(n+1)\\ & = A(N)f(N) - A(0) f(1) - \sum_{n=1}^{N-1} A(n) (f(n+1)-f(n)) \end{align*} (The above is nothing but the discrete version of integration by parts).

$$\sum_{n=1}^{N} a(n) f(n) = \int_{1^-}^{N^+} f(t) d(A(t)) = f(t) A(t) \rvert_{1^-}^{N^+} - \int_{1^-}^{N^+} A(t) f'(t) dt$$ (The second integral can be interpreted as a Riemann-Stieltjes integral.)



$$S_n=\sum_{k=1}^n \sin k \;\; S_0=0$$


$$\sin k=\sum_{i=1}^{k}\sin i -\sum_{i=1}^{k-1}\sin i=S_k-S_{k-1}$$


$$\sum_{k=1}^{n}\frac{\sin k}{k}=\sum_{k=1}^{n}\frac{S_k-S_{k-1}}{k}$$

We aim to show this is $$=\frac{S_n}{n}+\sum_{k=1}^{n-1}\frac{S_k}{k(k+1)}$$

Set $a_k=\frac{1}{k}$ Then

$$\frac 1 {k(k+1)}=-\left(\frac{1}{k+1}-\frac 1 {k}\right)=a_{k+1}-a_k$$

So the formula in question is


which is indeed Abel's summation by parts

$$\sum_{k=0}^na_kb_k=b_nA_n-\sum_{k=0}^{n-1} A_k(b_{k+1}-b_k)$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.